2012
DOI: 10.1590/s0102-311x2012000100014
|View full text |Cite
|
Sign up to set email alerts
|

Ten-year trends in prevalence of asthma in adults in southern Brazil: comparison of two population-based studies

Abstract: There are discrepancies in the literature regarding time trends in the occurrence of asthma in adults. This study compared asthma prevalence in two cross-sectional studies with a ten-year interval in Pelotas, Rio Grande do Sul State, Brazil. The first, in 2000, included 1,968 individuals, and the second, in 2010, 2,466 adults (20-69 years

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 22 publications
(26 reference statements)
2
5
0
7
Order By: Relevance
“…Recent studies have shown similar trends. In a smaller city from Brazil, the prevalence of wheezing and shortness of breath in the last 12 months remained stable over a ten year period [10]. The same stabilization has been described by Zollner et al in Germany, in a study conducted about current wheezing and asthma between 1992 and 2001 [11].…”
Section: Discussionsupporting
confidence: 69%
“…Recent studies have shown similar trends. In a smaller city from Brazil, the prevalence of wheezing and shortness of breath in the last 12 months remained stable over a ten year period [10]. The same stabilization has been described by Zollner et al in Germany, in a study conducted about current wheezing and asthma between 1992 and 2001 [11].…”
Section: Discussionsupporting
confidence: 69%
“…The prevalence of self-reported asthma in the previous year has been reported to be 4.7% ( 13 ) and 5.2%. ( 14 ) In the present study, by combining the questions regarding the diagnosis of asthma (no specific recollection period) and symptoms in the previous year, we found that 4.5% of those who were 20 years of age or older reported this condition. In addition, when analyzing that age group, we found significant differences between the genders in terms of the prevalence of asthma; this finding is consistent with those of previous studies, ( 13 , 14 ) the prevalence of asthma being higher among females (7.1% vs. 4.3%; p = 0.002).…”
Section: Discussionsupporting
confidence: 48%
“…( 14 ) However, the criteria used in those studies in order to define the outcome differ from those used in the present study, and it is therefore difficult to compare the studies in terms of the reported prevalence. The prevalence of self-reported asthma in the previous year has been reported to be 4.7% ( 13 ) and 5.2%.…”
Section: Discussionmentioning
confidence: 86%
“… 8 However, studies describing asthma prevalence associated factors for adults are limited to two publications, restricted to the urban area of Pelotas city, South region of Brazil, conducted in 2000 and 2010. 7 , 9 …”
Section: Introductionmentioning
confidence: 99%